Effect of Hospital Effluents and Sludge Wastewater on Foundations Produced from Different Types of Concrete - Aamer Najim Abbas; Lubna M. Abd; Muhannd W. Majeed (Civil Engineering Journal, 2019)
In last decades, there is an insufficiency of fresh water and construction works are increasing day by day consuming large amount of fresh water. Therefore research is processing on to employ the treated domestic wastewater in the preparation and curing of concrete. In this investigation, the concrete slab specimens casted with normal strength concrete and modified reactive powder concrete. The concrete specimens cast by using fresh water, wastewater, and hospital effluents water. The specimens cured in all water types for 28days and 56 days. At 28days curing with wastewater, a decrease in punching shear strength was observed from 24 kN in case of curing with fresh water to 21 kN and 20 kN in case of curing with wastewater and hospital effluents water respectively. Highest strength is exhibited by 56 days curing age, it was recorded about 32 kN, 24 kN and 23 kN punching shear strength of specimens cured with fresh water, wastewater and hospital effluents water respectively. The excess quantity of bicarbonates in treated domestic wastewater as curing water results a decrease in compressive strength of concrete specimens. Appearance of first crack was also affected significantly by using wastewater and hospital effluents water as curing water; 7.5 kN, 6.5 kN and 6 kN were the first crack loads of normal strength concrete panels cured with fresh water, wastewater and hospital effluents water, and 11 kN, 10 kN and 7.5 kN were the first crack loads of modified reactive powder concrete cured with fresh water, wastewater and hospital effluents water.